White light-emitting properties of NaGdF4 nanotubes through Tb3+, Eu3+ doping1. Issue 40 (28th October 2015) - Liu, Lu; Liang, Yimai; Li, Linlin; Zou, Lianchun; Gan, Shucai
<x xml:space="preserve">Abstract</x> White light emission can be realized in a single-phase NaGdF4 host by reasonably adjusting the relative doping concentrations of Tb3+ and Eu3+ under ultraviolet excitation.